Tumor inhibition or tumor promotion? The duplicity of CXCR3 in cancer - Russo, Eleonora; Santoni, Angela; Bernardini, Giovanni (Journal of leukocyte biology, 2020)
Tumor tissue includes cancer cells and normal stromal cells such as vascular endothelial cells, connective tissue cells (cancer associated fibroblast, mesenchymal stem cell), and immune cells (tumor‐infiltrating lymphocytes or TIL, dendritic cells, eosinophils, basophils, mast cells, tumor‐associated macrophages or TAM, myeloid‐derived suppressor cells or MDSC). Anti‐tumor activity is mainly mediated by infiltration of NK cells, Th1 and CD8+ T cells, and correlates with expression of NK cell and T cell attracting chemokines. Nevertheless, cancer cells hijack tissue homeostasis through secretion of cytokines and chemokines that mediate not only the induction of an inflamed status that supports cancer cell survival and growth, but also the recruitment and/or activation of immune suppressive cells. CXCL9, CXCL10, and CXCL11 are known for their tumor‐inhibiting properties, but their overexpression in several hematologic and solid tumors correlates with disease severity, suggesting a role in tumor promotion. The dichotomous nature of CXCR3 ligands activity mainly depends on several molecular mechanisms induced by cancer cells themselves able to divert immune responses and to alter the whole local environment. A deep understanding of the nature of such phenomenon may provide a rationale to build up a CXCR3/ligand axis targeting strategy. In this review, we will discuss the role of CXCR3 in cancer progression and in regulation of anti‐tumor immune response and immunotherapy. Review on how CXCR3 ligands can shape anti‐tumor immune responses and tumor growth and of the promising possibility to target these molecules for cancer immunotherapy.